Simple method for detecting fluconazole-resistant yeasts with chromogenic agar. - Patterson, T F (1996)
A method for detecting fluconazole-resistant yeasts was developed that uses chromogenic agar containing fluconazole. Yeasts were plated on media with fluconazole at 0, 8, and 16 micrograms/ml. On media without fluconazole, normal growth of susceptible yeasts (defined as those having a fluconazole MIC of < 8 micrograms/ml) was detected, while fluconazole-containing media suppressed susceptible strains and normal colonies of resistant yeasts (fluconazole MICs of > or = 8 micrograms/ml) were detected. This method was used to screen for resistance in oropharyngeal candidiasis. Isolates having fluconazole MICs of > or = 8 micrograms/ml and < 8 micrograms/ml were correctly predicted in 43 of 45 cultures and 115 of 116 cultures, respectively. This screening method appears to be rapid and sensitive for detection of fluconazole-resistant yeasts.